A comparative study of serum lipid profile in preeclampsia and normotensive pregnancy in third trimester and their fetomaternal outcome - Kumari, Pooja; Chouhan, Madhubala; Jakhar, Balveer; Sharma, Garima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Preeclampsia is a common medical complication in pregnancy in developing countries. It is one of the most common causes that lead to maternal and fetal morbidity and mortality. Incidence of preeclampsia in world is 3-5%.1 In India preeclampsia complicates 5-15% of pregnancies. As a result of these changes serial alteration in lipid profile, mainly increase in serum triglycerides, cholesterol occurs in pregnant women. Methods: After IEC clearance and taking informed written consent from the patients, present study was conducted at the Department of Obstetrics and Gynaecology in PDZH, RNT Medical College, Udaipur from December 2020 to June 2022. Results: Study result based on 100 pregnant women with pre-eclampsia (BP >140/90 mm of Hg) as cases and 100 normotensive pregnant women (BP <140/90 mm of Hg) as controls. Cases had significantly higher total cholesterol (219.21±63.13 vs. 176.24±31.33, P<.0001), significantly higher triglycerides (mg/dL) (208.35±79.32 vs. 166.41±29.6, P<.0001), significantly higher LDL (mg/dL) (133.7±39.81 vs. 103.96±18.38, P<.0001), and significantly lower HDL (mg/dL) (43.29±7.09 vs. 50.18±8.15, P<.0001) in comparison to control. Conclusions: Women with pre-eclampsia had significantly higher serum Cholesterol, LDL, TG and significantly lower HDL in comparison to healthy pregnant women. There was a significant increase in the serum Cholesterol, LDL, TG in patients from mild to severe pre-eclampsia.